MicroRNA‐125b expression and intrahepatic metastasis are predictors for early recurrence after hepatocellular carcinoma resection. Issue 4 (5th December 2017) - Shimagaki, Tomonari; Yoshizumi, Tomoharu; Harimoto, Norifumi; Yoshio, Sachiyo; Naito, Yutaka; Yamamoto, Yusuke; Ochiya, Takahiro; Yoshida, Yoshihiro; Kanto, Tatsuya; Maehara, Yoshihiko
Abstract : Aim: Early hepatocellular carcinoma (HCC) recurrence after curative resection is a known poor prognostic factor. We aimed to identify microRNAs associated with recurrence after curative HCC resection. Methods: To identify risk factors for early recurrence and metastasis, 694 patients who underwent primary curative HCC resection were analyzed. We evaluated microRNA expression in cancerous and non‐cancerous tissues by microarray and quantitative PCR analyses using 16 HCC samples. We defined patients who had a recurrence within 1 year of resection as the early recurrence (ER) group, patients who had a recurrence within 1–5 years as the late recurrence (LR) group, and patients who did not recur during the 5‐year observation period as the no recurrence (NR) group. We examined the relationship between microRNA expression and clinical features. Results: Multivariate analysis revealed that α‐fetoprotein >31 ng/mL, tumor size >4 cm, and intrahepatic metastasis (IM) were significant factors. Afterwards, microarray analyses revealed that microRNA (miR)‐125b‐5p and miR‐148a‐3p were significantly downregulated in recurrent cases. The ratio of miR‐125b‐5p expression in cancerous versus non‐cancerous tissue (miR‐125b ratio), but not miR‐148a‐3p, was significantly lower in the ER group. Early recurrence was associated with reduced overall survival compared with the LR and NR group. The miR‐125b ratio was significantly lower in the ER group than in the LR and NR groups. Multivariate analysis showed that a low miR‐125b ratio and IM were independently associated with ER and disease‐free survival. Conclusions: Assessing tissue miR‐125b‐5p expression and IM is useful for stratifying patients at risk of early HCC recurrence after curative resection.